POSISI DAN RELASI AKTOR DALAM INISIASI PERLUASAN TAPAK KONSERVASI BERBASIS “IMPORTANT BIRD AND DIVERSITY AREAS” DI PEGUNUNGAN JAWA BAGIAN BARAT - Desmiwati Desmiwati; Yoppie Christian; Adi Widyanto; Andriansyah Andriansyah (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
Western Java’s upland is a sanctuary of importants biodiversity in Indonesia for avifaunas, primates and mammals. Particularly for avifaunas, the upland becomes the last sanctuary after the disturbance and distraction by anthropogenic activities. This kind of situation raises needs to expand conservation site as an effort to protect the biodiversities. This research aims to find opportunities through the lens of actors. This research uses Collaboration/ Conflict, Legitimacy, Interest and Power (CLIP) frameworks to identifiy responses, positions ,and inter-actor relations if expansion of conservation site is initiated based on the Important Birds and Diversity Areas (IBAs). The result shows that out of five clusters of research sites, the Important Bird and Diversity Areas of Southern Bandung has some indicators which enable collaboration in the expansion. From the actor perspectives, there are five existing preconditions to support the implementation for expansion, namely availability of landscape, willingness of the right holders, opportunities for sharing management, concordance with provincial spatial plan, and low conflict potentials. To implement the expansion, participatory multistakeholders mapping on selected areas need to be conducted and action plan for integrated landcape management should be implemented